2003
DOI: 10.1136/thorax.58.6.533
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms in patients with treated hypothyroidism and inflammatory bowel disease

Abstract: Background: Patients with idiopathic chronic cough and unexplained airflow obstruction in non-smokers have been shown to have an increased prevalence of hypothyroidism and other organ specific autoimmune disorders. Whether patients with hypothyroidism have an increased prevalence of respiratory symptoms is unknown. Methods: The prevalence of respiratory symptoms was assessed in 124 patients with treated hypothyroidism recruited from primary and secondary care, 64 outpatients with inflammatory bowel disease, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 16 publications
2
40
1
3
Order By: Relevance
“…Association between asthma and IBD was also suggested by Hemminki et al [21]. Another study that showed a significantly increased prevalence of respiratory symptoms in subjects with IBD was one by Birring et al [22]. They compared the frequency of respiratory symptoms in 64 IBD patients and 124 healthy persons.…”
Section: Epidemiologymentioning
confidence: 89%
See 1 more Smart Citation
“…Association between asthma and IBD was also suggested by Hemminki et al [21]. Another study that showed a significantly increased prevalence of respiratory symptoms in subjects with IBD was one by Birring et al [22]. They compared the frequency of respiratory symptoms in 64 IBD patients and 124 healthy persons.…”
Section: Epidemiologymentioning
confidence: 89%
“…In the study by Birring et al [22], there was a trend for those with active inflammatory bowel disease to report more symptoms, compared to those whose IBD was in remission. Yilmaz et al [26] found association of increased respiratory symptom score with high endoscopic activity index in UC patients, but there was no correlation between respiratory symptoms and clinical activity of bowel disease.…”
Section: Respiratory Disease Depending On Ibd Activitymentioning
confidence: 99%
“…The most common findings include bronchial wall thickening and bronchi-CD and 19 UC patients [25,26] . In a case control study of 64 IBD patients compared to 1346 controls, after adjustment for age, sex and smoking status, IBD patients were more likely to report shortness of breath and sputum production and to a lesser degree, cough [odds ratio (OR) respectively 3.4, 2.5, 1.8], highlighting the importance of relative clinical awareness [27] . Moreover, Higenbottam et al [28] described a respiratory exacerbation with cough and shortness of breath several years after coloproctectomy with the primary IBD in remission.…”
Section: Radiology -High Resolution Computed Tomographymentioning
confidence: 99%
“…The association between cough and autoimmune disease is also supported by a 2 to 3 fold increase in cough symptoms in patients with treated hypothyroidism compared with controls. 19 Furthermore, studies investigating airway function of patients with hypothyroidism have found evidence of airway inflammation and heightened cough reflex sensitivity. 20 A high prevalence of autoimmune disease has also been reported in patients with unexplained fixed airflow obstruction.…”
Section: Idiopathic Chronic Cough and Autoimmune Diseasementioning
confidence: 99%